Pelatihan Keterampilan Komunikasi Interpersonal dalam membantu Permasalahan Santri di Pondok Pesantren Assalafi Miftakhul Huda Kabupaten Grobogan, Jawa Tengah - Afriyadi Sofyan; Awalya Awalya; Eko Nusantoro; Dian Purbo Utomo (Indonesian Institute For Counseling, Education and Therapy, 2020)
Students at the Islamic boarding school for 24 hours and have limited interactions in the boarding school environment are very risky to experience various personal, social and learning problems. Interpersonal Communication Skills Training at the Assalafi Miftakhul Huda Islamic Boarding School in Grobogan Regency provides training to caregivers (senior santri) who will serve as peer guidance. Caregivers are trained to be ready listeners and good friends to help with problems related to other students. Active listening techniques are a specific skill that is trained by caregivers in helping students. Training activities were carried out using lecture and simulation methods on September 13, 2020. The training participants were 50 male and female caregivers. The participants seemed very enthusiastic during the activity. The results of the instrument analysis show that the participants reported the content of the material and the suitability of the written material and the presentation that the team did was the best point in this service activity. On the other hand, the participants stated that the training was too short and felt that they had not had the opportunity to practice. This is a recommendation for the implementation of further community service and needs to be done in a programmed and more intensive manner.